Assessment of anti-atherosclerotic effect of Eurycoma longifolia extract on high-fat diet model in rats. I: Histological study - Al-Jaufi, Fakhria; Al-Ani, Imad M; Saxena, Anil Kumar; Talib, Norlelawati A.; H. Mokhtar, Rafidah; Ku-Zaifah, Norsidah (The Spanish Society of Anatomy, 2016)
The objective of this study was to examine the effect of Eurycoma longifolia (EL) extract on intima media thickness (IMT) of aorta in Sprague Dawley (SD) rats fed with high-fat diet. Twenty healthy male SD rats were divided into 4 groups of 5 animals each and treated for 12 weeks as follows: Group ND was given only normal diet, Group NDEL was given normal diet and EL, Group HFD was given only high fat diet, Group HFDEL was given HFD and EL extracts. The aortic thicknesses of the intima media were photographed and measured with Dino-Capture® 2.0.In this study, the HFD produced obvious atherosclerotic plaque; treatment with aqueous extract of EL has reduced the size and formation of atherosclerotic plaque. The aortic IMT was more significantly increased in the HFD group than that of ND (p < 0.05); on the other hand, the aortic IMT was more significantly reduced in HFDEL group than that of HFD group (p < 0.05). It is concluded that the aqueous extract of EL significantly attenuated the formation of atherosclerotic plaques in the aorta of rats and preserved the vascular structure.